Foreword - Thomas Neumann (Nordic Journal of Commercial Law, 2018)
Dear Readers. Now that the journal had its baptism of fire with the publication of a special issue on CSR, the time has come to wish you all happy new year and to publish this first regular issue under the auspices of Aalborg University. This slightly delayed second issue of 2017 contains four contributions. In the first contribution, Ulrich Schroeter, with whom I have shared research interests for a long time, analyses the cut-off period contained in 1980 UN Sales Convention’s Article 39(2) and its relation to domestic limitation periods with a particular focus on court practice. In the spirit of the journal’s ambition of making high quality publications available to a wide audience, I proudly publish this revised version of Ulrich Schroeter’s article which was first published in a tribute to Joseph M. Lookofsky in 2015. In the second contribution Katerina Mitkidis and I address issues relating to what has been called Americanisation of contracts in the Nordic region. Specifically, we address the curious use of entire agreement clauses in contracts governed by Danish law – an entirely different legal context than the American one that the clauses typically are utilised in. I owe it to my dear colleague Katerina Mitkidis to emphasise that she has been the lead author on this contribution from start til finish. In the third contribution, Michele Giannino analyses the challenges arising from public aid to airports given in the form of public service compensation. This contribution is the first publication since the journal’s revival written by – if I may – an outsider, in the sense that Michele Giannino is an Italian qualified lawyer with a background also from Leicester and London. It pleases me to publish Gianino’s view on an EU law regulated problem in a Nordic context. The fourth contribution is a revival of an old NJCL tradition. The journal grew from the community surrounding my friend and academic mentor Albert H. Kritzer, who was the founder and editor of the CISG Database hosted by Pace Law in New York. In the beginning of the journal’s history, several articles addressing issues relating to the CISG was published, including also the opinions of the CISG Advisory Council. However, during the years this tradition was lost. By publishing the CISG Advisory Council’s opinion number 17 on limitation and exclusion clauses I revive the journal’s tradition of being the Advisory Council’s “publisher”. I would like to thank all the contributors of NJCL: the peer reviewers whom I give very short deadlines, the authors who submitted their manuscripts, and my assistant Signe Lindbjerg without whom the task of running this journal would be insurmountable. I also thank Dreyers Fond for sponsoring the journal, making it possible to provide open access to good research for anyone, anywehere in the world.